IICA marketing and agroindustry study: pilot phase report - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The pilot phase of the IICA Marketing and agroindustry project consisted of field work undertaken by outside consultants in four selected sample countries in Latin America and the Caribbean (LAC) and in North America. The field data collection was managed by the Prime Consultants, who are also responsible for data analysis and overall conclusions from this phase.